Development, progress and economic growth - Bresser-Pereira, Luiz Carlos (2013)
Progress was an idea of the 18th century; development, a project of the 20th century that continues into the 21st century. Progress was associated with the advance of reason, development with the fulfillment of the five political objectives that modern societies set for themselves: security, freedom, economic well-being, social justice and protection of the environment. Today we can view progress and development as equivalent. Both were products of the capitalist revolution, and of the economic development that began with it. Economic development or growth, in its turn, is the process of capital accumulation with the incorporation of technical progress that, mainly through productive sophistication and the increase of the value of labor, increases wages and improves standards of living. The five objectives that define development, as well as the three social instances existing in society change in an interdependent way.